(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: private pharmacies play an important role in the drug supply system to people. Objective: describe the results of managing drug purchasing activities and factors related to correct knowledge of SOPs at private pharmacies in Phu Nhuan district, Ho Chi Minh City in 2023. Method: descriptive cross-sectional study conducted on 110 private pharmacies and 386 drug retailers at private pharmacies in Phu Nhuan district, Ho Chi Minh City, from November 2022 - June 2023. Results: the percentage of pharmacists with correct knowledge about SOPs for selling prescription drugs is 33.68%, and 42.49% for non-prescription drugs. There is a relationship between correct knowledge of SOPs for selling prescription drugs and: gender; qualification; professional experience; working time every day and received training on medical law knowledge in the past 2 years (p<0.05). There is a relationship between correct knowledge of SOPs for selling non-prescription drugs and: age; sex; qualification; Professional experience and working time per day (p<0.05). Conclusion: the research results will help policy makers propose intervention solutions to improve the quality of drug purchasing activities at private pharmacies, to ensure safe drug supply activities, effectively reach consumers.